Metagenomics study of soil microorganisms involved in the carbon cycle in a saline–alkaline meadow steppe in the Songnen Plain in Northeast China - Xiao, Huichuan; Wei, Yinzhu; Sun, Xuetong; Song, Xue; Liu, Jielin; Bai, Zhenjian; Hu, Guofu; Qin, Ligang (Frontiers in Microbiology, 2024)
Soil microorganisms play an important role in regulating and contributing to carbon cycling processes in grassland ecosystems. Soil salinization is one of the major problems causing soil degradation, and its effects on carbon cycle immobilization-related functional genes in soil microorganisms remain unknown. Therefore, we conducted a metagenomic study to examine how different levels of salinity in the Songnen grassland affect the diversity of soil microorganisms and functional genes related to carbon cycling. It was found that the relative abundance of Ascomycetes increased with increasing soil salinity, while the relative abundance of Aspergillus and Sclerotinia decreased. In addition, the relative abundance of functional genes associated with carbon cycle fixation decreased with increasing soil salinity, with a significant increase in the relative abundance of the glycoside hydrolase (GH)130 family and a significant decrease in the relative abundance of soil carbohydrases belonging to the GH3 and GH55 families. Intensification of grassland salinization reduced the diversity of bacteria and fungi, and affected the diversity of functional genes related to carbon cycle immobilization by reducing the total diversity of bacteria, as assessed using a structural equation model (SEM). These results indicate that increasing salinity has a negative feedback effect on carbon cycling in grassland soils, and that microbial diversity and functional gene diversity are highest in moderately saline grasslands (MDS). The results elucidate the mechanisms by which salinization of grassland soils affects microbial and genetic diversity associated with carbon cycle fixation. They provide a theoretical framework for grassland soil carbon sequestration and degradation restoration.